Cosmic sculpture: a new way to visualise the cosmic microwave background. (28th October 2016) - Clements, D L; Sato, S; Fonseca, A Portela
Abstract: 3D printing presents an attractive alternative to visual representation of physical datasets such as astronomical images that can be used for research, outreach or teaching purposes, and is especially relevant to people with a visual disability. We here report the use of 3D printing technology to produce a representation of the all-sky cosmic microwave background (CMB) intensity anisotropy maps produced by the Planck mission. The success of this work in representing key features of the CMB is discussed as is the potential of this approach for representing other astrophysical data sets. 3D printing such datasets represents a highly complementary approach to the usual 2D projections used in teaching and outreach work, and can also form the basis of undergraduate projects. The CAD files used to produce the models discussed in this paper are made available.